2015
DOI: 10.1364/oe.23.012337
|View full text |Cite
|
Sign up to set email alerts
|

Focusing and imaging in microsphere-based microscopy

Abstract: Microsphere-based microscopy systems have garnered lots of recent interest, mainly due to their capacity in focusing light and imaging beyond the diffraction limit. In this paper, we present theoretical foundations for studying the optical performance of such systems by developing a complete theoretical model encompassing the aspects of illumination, sample interaction and imaging/collection. Using this model, we show that surface waves play a significant role in focusing and imaging with the microsphere. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 31 publications
3
29
0
1
Order By: Relevance
“…Based on a solid‐immersion concept ( n o ≈ n s ), the maximal diffraction‐limited resolution available for high‐index ( n s ∼ 2.0) barium titanate glass (BTG) microspheres can be estimated as ∼ λ /4. This estimation is consistent with the calculations of focusing and imaging properties of mesoscale spheres.…”
Section: Introductionsupporting
confidence: 90%
“…Based on a solid‐immersion concept ( n o ≈ n s ), the maximal diffraction‐limited resolution available for high‐index ( n s ∼ 2.0) barium titanate glass (BTG) microspheres can be estimated as ∼ λ /4. This estimation is consistent with the calculations of focusing and imaging properties of mesoscale spheres.…”
Section: Introductionsupporting
confidence: 90%
“…Details on SRE are outside the scope of this review and will be presented in a separate publication elsewhere. It is noted that Haong et al also reported super-resonance effect using same experimental parameters as in Fig.1 (a=2.37 um, n=1.46), they found that a ~0.24λ resolution can be achieved at wavelength 402.292 nm, in excess of solid immersion resolution limit of λ/ (2*1.46) =0.34λ) [43]. We believe SRE is vital to microsphere super-resolution imaging.…”
Section: 11) Photonic Nanojetsupporting
confidence: 57%
“…Recent studies have shown that the surface waves play a significant role in focusing and imaging with the microsphere [26]. Therefore, it should be emphasized that, besides the super-strength focus effects discussed in this paper, other mechanisms must be contributing to the microsphere imaging.…”
Section: Resultsmentioning
confidence: 85%